The art collector's guidebook - Duldulao, Manuel D. (Dagupan City University of Pangasinan, 2005)
Contents: All about arts. Making and selling art collections. Fine art of collecting objects of beauty. Anecdote with art and lively social history.
Purpose: "It is used to offer guidance on every aspect of collecting, from the cultivation of an 'eye' for the great art to its acquisition."
Keywords: Art -- Collectors and collecting -- Handbooks, manuals, etc; Art -- Collectors and collecting -- Philippines -- Handbooks, manuals, etc; Art as an investment